"Burnt out" dilated hypertrophic cardiomyopathy causing acute LVAD thrombosis. Issue 6 (9th April 2015) - Sivathasan, Cumaraswamy; Tan, Teing E. E.; Sim, David; Kerk, Ka Lee
Key Clinical Message Case report illustrates obstruction encountered in a patient with end‐stage dilated hypertrophic cardiomyopathy (HCM) who underwent LVAD implantation. The morphology reversed in early postoperative period to HCM. Pump replacement required coring of the ventricular muscle. Dilated end‐stage hypertrophic cardiomyopathy can revert back to the original morphology on decompression.